Effects of the Junction Functionality and Chain Entanglements in Chemomechanical Behavior of Polyelectrolyte Gels. (26th May 2015) - Ma, Lianhua; Yang, Qingsheng; Yang, Chunhui
Abstract : By considering the functionality of junctions and entanglements of polymer chains for polyelectrolyte gels, a new free energy density function is presented via combining Edwards-Vilgis slip-link model with Flory-Huggins theory. On this basis, the effects of the functionality of network junctions and entanglements of polymer chains are systematically analyzed for free swelling of a cubic polyelectrolyte gel and constrained swelling of a blanket layer of the gel. Analytical results show that the functionality of junctions and chains entanglements plays an important role in the coupled chemomechanical deformation of polyelectrolyte gels.